Faktor-Faktor yang Mempengaruhi Kinerja Pegawai Pelayanan Hewan dan Peternakan Kabupaten Pesisir Selatan - Yulina Eliza; Yass Andria (Universitas Bumigora, 2022)
This study aims to see the influence of (1) Organizational culture on Employee Performance (2) Job satisfaction on Employee Performance (3) OCB on Employee performance (4) Organizational culture, job satisfaction and OCB together affect the performance of Employees of the Livestock and Animal Health Service of South Coast District. The population in this study across all employees was 65 people. Data processing uses Multiple Linear Regression. The results of this study show that (1) Organizational culture has a significant positive influence on Employee performance (2) Job satisfaction has a positive and significant influence on employee performance (3) OCB has a positive and significant influence on Employee performance (4) Organizational Culture, Job Satisfaction and OCB together have a positive and significant effect on employee performance in DPKH Pantai Selatan Regency. It is expected that agency management must pay attention to organizational culture, employee job satisfaction, and create good job satisfaction in the agency, because job satisfaction is a big influence in improving performance. Because to achieve better productivity and achievement of agency goals, good job satisfaction, organizational culture and good OCB are needed.